An econometric study of public policy applied to renewable energy, economic growth and taxation - Mette, Jehu A. (Kansas State University, 2021)
This dissertation consists of three essays on public policy related to renewable energy, economic growth and tax policy. Each chapter is implemented with a different econometric method to investigate the policy question of interest. The first chapter studies the effect of renewable energy utilization on many food price categories in relation to the Energy Policy Act of 2005. The second chapter investigates the link between public education expenditures and long term economic growth in the context of countries' institutional quality, while the third chapter focuses on the impact of the 2012 Kansas tax reform on state employment across industries. The first essay, co-authored with Dr. Bebonchu Atems, examines the link between renewable energy consumption and consumer food prices in recent years. The Energy Policy Act of 2005 increased the amount of biofuel that must be mixed with commercial gasoline sold in the U.S. to 7.5 billion gallons by 2012. The Energy Independence and Security Act of 2007 further increased this requirement to 36 billion gallons by 2022. This increase in the production and consumption of biofuels, in particular, and renewable energy sources, in general, may compel farmers to divert significant quantities of cropland away from food and feed crops, which, in turn may lead to a rise in crop prices, feed prices, meat and poultry prices, and hence, overall food prices. Employing structural vector autoregression (SVAR) models and monthly U.S. data for the period 1974:01 to 2019:12, this paper examines, empirically, the impact of renewable energy consumption on food prices. We find, in general, that renewable energy shocks have no significant impact on food prices. For the period since the passage of the Energy Policy Act, however, shocks to biomass and wind energy consumption raise food prices significantly and persistently. In the second econometric essay, co-authored with Dr. William Blankenau, we utilize panel and cross-sectional data to explore the link between education spending and long run growth among countries with different institutional quality. The economics literature suggests that education spending and strong institutions both positively affect economic growth. However, their combined effect has received considerably less attention. To explore this, we derive a growth regression from an endogenous growth model constructed to map the link between education spending, institutional quality and growth outcomes. It would be natural to expect that the marginal effect of education spending increases with strong institutions. Our results suggest that education spending and strong institutions instead operate as substitutes in generating growth, especially in rich and developing countries. The explanation could be that growth can arise from better skills due to higher education spending or from enhanced economic activity due to stronger institutions. This relationship could suggest a certain redundancy, especially when countries with high institutional quality also invest substantially in education spending. We emphasize that the implication is not that one is less important or has a negative effect on growth. In the third essay, which is co-authored with Dr. Ross Milton, we revisit the impact of one of the largest state tax reforms in history. In 2012, the state of Kansas eliminated taxation for business income and lowered marginal tax rates on other personal income sources. Contrary to predictions of the new legislation's proponents, prior work has established that the tax reform had no significant impact on the aggregate state employment or real economic activity. In this study, we ask whether the effect was the same for high pass-through industries and other sub-samples of interest to policymakers. Overall, we find no aggregate employment increase, but rather, job losses in a few industry groups. We find that even after excluding the aircraft manufacturing, the oil and energy industries as well as the agricultural sector, the aggregate state employment did not increase. We further test whether industries with a high concentration of pass-through employment experienced more job gains. We fi nd that while a positive link exists between high pass-through concentration and job gains, the link is never significant regardless of time horizons or specifications while income re-characterization cannot be ruled out.
Keywords: Applied econometrics; Public policy; Macroeconomics; Education economics; Institutions; Renewable energy